PbS-ZnO Solar Cell: A Numerical Simulation - Jaymin Ray; Tapas K. Chaudhuri; Chetan Panchal; Kinjal Patel; Keyur Patel; Gopal Bhatt; Priya Suryavanshi (Журнал нано- та електронної фізики)
Nanoscale PbS, especially quantum dots (QDs) are of interest in applications, such as, solar cells and photodetectors because of tunability of band gap from 0.5 to 3 eV. Recently, ZnO/PbS solar cells with 8.55 % conversion efficiency have been reported with films made deposited from ligand exchanged PbS QDs. However, nanocrystalline PbS is easier to fabricate than QDs. This paper reports theoretical investigation into the use of nanocrystalline PbS in place of QDs as solar cell absorber. Solar cells with a structure of SLG/ITO/ZnO or CdS/PbS/Al was simulated using SCAPS software. We have used two n-type materials one is ZnO and second is CdS. The comparative simulated device performance was studied by current-voltage (I-V) characteristics and quantum efficiency (QE). The final results reveal a power conversion efficiency of 18.5 % for solar cells with p-PbS as absorber and n-ZnO as buffer and 16.8 % for n-CdS buffer layer.